Lasse Braun, rape scenarios, and Swedish censorship: a case study of two 8-mm porn films featuring rape. Issue 1 (2nd January 2017) - Larsson, Mariah
ABSTRACT: This article examines rape scenarios in two pornographic 8-mm films by Lasse Braun: White Fantasies / Black Power (1969) and Cerimony (1971). Furthermore, it begins an exploration of Lasse Braun, an important figure in late-1960s and early-1970s pornography. Finally, because both films were censored by the Swedish National Board of Film Censors, the article considers their specific national-historical contexts including the legal situation for pornography in Sweden and the shifting discourses on rape in the 1970s, to open up a discussion of whether the elimination of violence in pornographic representations actually makes them less misogynist. The censorship decisions clearly echoed anxieties about race and gender provoked by these two films. A closer look at the films reveals a knowing approach, not only to sexual fantasies, but also to contemporary political and aesthetic movements.